Nutrition Education and Dietary Consultation for Heart Disease Management in the Elderly in Gubeng District, Surabaya - Hafid, Fahmi; Rusyadi, Luthfi; Nur Kholifah, Siti; Sumasto, Hery; Taufiqurrahman, Taufiqurrahman; Soesanti, Inne; Intiyati, Ani; Shofiya, Dian; Hatijah, Nur; Marina Pengge, Nuning; Mujayanto, Mujayanto; Faisal Nugroho, Riezky; Hindaryani, Nurul; Saputri, Khristine; Eka Ratnasari, Devi; Halimah, Husnul; Sariman, Sarina (Media Publikasi Cendekia Indonesia, 2025)
Heart disease is the leading cause of death in the elderly, mainly due to unhealthy diets and metabolic risk factors such as hypertension and diabetes. This nutrition education and dietary consultation program aims to increase the understanding and change of behavior of the elderly in implementing a healthy diet to prevent heart disease. The activity was held for one month in Gubeng District, Surabaya, involving 125 seniors, lecturers, and students. Intervention methods include interactive education, simulations, and personalized nutrition consultations. The evaluation results showed a significant increase in knowledge scores, changes in positive attitudes, and adoption of a healthier diet based on statistical analysis of the Paired t-Test and Wilcoxon Test (p < 0.05). Knowledge Improvement: The average knowledge score increased from 65.2 ± 10.1 to 82.7 ± 8.5, reflecting an increase of 26.9% (p < 0.05). Improved Attitudes: 85% of participants switched to a more positive outlook on adopting a heart-healthy diet, with the Likert scale rating increasing from 3.2 ± 0.8 to 4.5 ± 0.6 (p < 0.05). This program effectively improves dietary knowledge, attitudes, and behaviors among the elderly in Gubeng Regency. The sustainability of the program is advised through technology-based education and family involvement to improve the quality of life of the elderly sustainably.